2003
DOI: 10.1105/tpc.014563
|View full text |Cite
|
Sign up to set email alerts
|

A Growth Regulatory Loop That Provides Homeostasis to Phytochrome A Signaling[W]

Abstract: Phytochrome kinase substrate1 (PKS1) is a cytoplasmic protein that interacts physically with, and is phosphorylated by, the plant photoreceptor phytochrome. Here, we show that light transiently increases PKS1 mRNA levels and concentrates its expression to the elongation zone of the hypocotyl and root. This response is mediated by phytochrome A (phyA) acting in the very low fluence response (VLFR) mode. In the hypocotyl, PKS1 RNA and protein accumulation are maintained only under prolonged incubation in far-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 48 publications
6
114
0
1
Order By: Relevance
“…In agreement with this view, the effect of enhanced PKS1 levels is larger in the pks2 background (i.e. in the absence of the negative regulation imposed by PKS2) [52]. These loops are therefore a source of homeostasis.…”
Section: Regulatory Loopssupporting
confidence: 60%
“…In agreement with this view, the effect of enhanced PKS1 levels is larger in the pks2 background (i.e. in the absence of the negative regulation imposed by PKS2) [52]. These loops are therefore a source of homeostasis.…”
Section: Regulatory Loopssupporting
confidence: 60%
“…These include FHY1 and FHY1-LIKE, two proteins necessary for the import of phyA into the nucleus upon light activation (see Supplemental Figure 1 online; Zeidler et al, 2004;Hiltbrunner et al, 2005Hiltbrunner et al, , 2006Zhou et al, 2005;Rosler et al, 2007;Genoud et al, 2008) and some members of the PKS1 and SPA1 protein family. The cytoplasmic PKS1 and 2 proteins, which can interact with phyA, show enhanced phyA-mediated VLFR and are also involved in blue light-dependent phototropism (Fankhauser et al, 1999;Lariguet et al, 2003). SPA1, which together with COP1 is needed for the degradation of several light signaling factors, is also important for VLFR as the hypersensitive phenotype of spa1 can also be observed under very low fluences (Hoecker et al, 1999;Fittinghoff et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pks1 and 2 mutants show enhanced phyA-mediated VLFR but are also involved in blue light-mediated phototropism (Lariguet et al, 2003(Lariguet et al, , 2006. Although GIGANTEA (GI) was first characterized as playing a role in the circadian clock and deetiolation under red light conditions, recent work showed that this protein is also important for hypocotyl growth, cotyledon opening, and germination under VLF conditions (Oliverio et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…X-Gluc (5-bromo-4-chloro-3-indolyl-beta-D-glucuronic acid, cyclohexylammonium salt) was purchased from X-GLUC DIRECT (WakeWeld, UK). Staining was performed as described elsewhere (Lariguet et al 2003). BrieXy, 72-hold seedling grown vertically in the dark were soaked in cold (4°C) acetone 90%, then rinsed and stained (5 min at 4°C and 12 h at 37°C) in a solution containing 2 mM XGluc, 2 mM ferrocyanide, 2 mM ferricyanide and 10 mM sodium phosphate buVer.…”
Section: Gus and Gfp Constructsmentioning
confidence: 99%